ING2 controls the G1 to S-phase transition by regulating p21 expression - Larrieu, Delphine; Ythier, Damien; Brambilla, Christian; Pedeux, Rémy (Cell cycle (Georgetown, Tex.), 2010)
ING2 (Inhibitor of Growth 2) is a candidate tumor suppressive protein frequently lost in human tumors. Recently, we have reported that ING2 downregulation impairs DNA replication forks progression and leads to genome instability. To better understand the tumor suppressive functions of ING2 and its role in the cell cycle, we downregulated its expression in cells and studied the consequences of this downregulation on the G1/S transition. We observed that the inhibition of ING2 expression accelerated the progression of cells from G1 to S phase, and was accompanied by a decrease of p21 expression. Moreover, we show that the regulation of p21 by ING2 is independent, of the tumor suppressive protein p53. Interestingly, this function seems to be unique for ING2 since its closest homologue ING1 does not regulate the G1/S transition. It has been suggested previously that ING2 may modulate the trimethylation of H3K4 at the promoter of p21. Accordingly, our results suggest that there may be a link between the regulation of the G1/S transition by ING2 and the level of H3K4Me3. All together, these results bring new information concerning the role of ING2 in the regulation of the cell cycle and suggest that it may play important roles in controlling several S phase checkpoints.